A Critical Discourse Analysis of Corporate Response to Trump’s Tariff Policy in CNN Coverage - Alfina Roisatul Isnaini; Ayu Ningtias; Dwi Puspita Sari; Eny Maulita Purnama Sari (EDU AKOMMEDIA : JURNAL ILMU PENDIDIKAN, 2026)
This research investigates the prompt reaction of corporation to the renewed tariff regulations enacted by president Trump in 2025, contentrating on presing adjustment tactics actoss different industy categories. By examining publik discosuresand finansial report from leading US firms, we record notable price hikes impacting consumer products, automotive items, and retail goods. Our results indicate that firms such as Walmart, ferrari, Ford, Best Bay, Mattel, and Prokter & Gameble have diclared or initiated price in creases between 5% & 10% due to tariff rates escalating to 25-145% o nan assortment of imported items. The study reveals that the costs associated with tariffs arlargely transferred to consumers instead of being absorbed by the bussinesses, with projected increases in household expenses estimeted at $1,155 to $1,397 each year. The polotical pressure from the administration urging companies to “absorb” the tariff costs has fostered conflict between economic realities and governmental demands. This study enhences the comprehension of the microeconomic pathwais of trade policy and offers practical evidence of the impacts of tariffs in modern US market.